2001
DOI: 10.1136/heart.86.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision in asymptomatic aortic valve stenosis: role of exercise testing

Abstract: Objective-To determine the prognostic value of exercise testing, valve area, and maximum transaortic pressure gradient in asymptomatic patients with aortic valve stenosis. Setting-The outpatient service of a tertiary referral centre for cardiology. Design-Prospective clinical study. Patients-66 consecutive patients with isolated severe aortic stenosis (aortic valve area < 1.0 cm 2 ) were selected over a 58 month period. Mean (SD) follow up was 14.77 (11.93) months. Interventions-At the initial visit Doppler ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
2
17

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(186 citation statements)
references
References 24 publications
6
161
2
17
Order By: Relevance
“…Our data parallel investigations that have documented the prognostic value of exercise duration in AR (6) and coronary artery disease (5) and its correlation with symptoms in patients with mixed MR and AR (24). They also suggest that exercise tolerance from ETT can be useful in detecting unreported symptoms from MR, as is true, and prognostically useful, among patients with aortic stenosis (25). Since patients may minimize activity without recognizing the cause, observation of exertional dyspnea by the clinician during ETT (found in almost a quarter of our patients during index testing) may be useful in defining subsequent management.…”
Section: Discussionsupporting
confidence: 86%
“…Our data parallel investigations that have documented the prognostic value of exercise duration in AR (6) and coronary artery disease (5) and its correlation with symptoms in patients with mixed MR and AR (24). They also suggest that exercise tolerance from ETT can be useful in detecting unreported symptoms from MR, as is true, and prognostically useful, among patients with aortic stenosis (25). Since patients may minimize activity without recognizing the cause, observation of exertional dyspnea by the clinician during ETT (found in almost a quarter of our patients during index testing) may be useful in defining subsequent management.…”
Section: Discussionsupporting
confidence: 86%
“…Il est démontré que 20 % à 30 % des patients porteurs d'une SA sévère asymptomatique présentent un test d'effort anormal [5,6].…”
Section: Test D'effort Conventionnelunclassified
“…La valeur prédictive positive de symptômes induits par l'exercice pour la survenue de symptômes spontanés dans les 12 mois était médiocre (57 %) dans le travail de Das et al, mais apparaissait meilleure (79 %) chez les patients jeunes physiquement actifs (< 70 ans) [12]. Bien que non spécifique, la survenue des autres symptômes (vertiges, angor, ou syncope), en particulier chez les patients âgés de moins de 70 ans entretenant une activité physique [12], prédit le développement rapide des symptômes dans la vie quotidienne dans l'année qui suit [5,6]. Un RVAo est alors recommandé (classe I C) quand le test à l'effort est positif [1].…”
Section: Symptômesunclassified
See 1 more Smart Citation
“…In addition, exercise‐induced drop in systolic blood pressure is a Class IIa indication for surgery1, 2 However, these recommendations are based upon multiple small reports with heterogeneous end points3, 9, 10, 11, 12, 13, 14, 15 In a recent study, we have demonstrated that in asymptomatic patients with severe AS and preserved left ventricular ejection fraction (LVEF), only 50% achieved 100% of age‐sex predicted exercise capacity; with exercise stress testing providing significant reclassification of longer‐term mortality risk16 In the past decade, novel echo parameters including reduced left ventricular global longitudinal strain (LV‐GLS)17, 18, 19 and valvuloarterial impedance (Zva)17, 19, 20 have also been associated with worse prognosis in patients with asymptomatic severe AS. However, no study has systematically evaluated the incremental prognostic impact of resting Zva and LV‐GLS on data obtained from exercise stress testing in patients with asymptomatic severe AS and preserved LVEF.…”
Section: Introductionmentioning
confidence: 99%